(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Long-term intake of high-fat food disrupts lipid metabolism, resulting in fat accumulation, obesity, and hyperlipidemia. Curcumin, active ingredients of turmeric plants, has been shown to possess potent antioxidant and hypolipidemic properties. The study was conducted to observe the effects of curcumin on butter induced hyperlipidemia, hematological values and physio-pathological alterations in liver and aorta in mice. A total of 40 Swiss Albino mice (Mus musculus), aged 28-30 days with an average body weight of 27g were randomly divided into 2 groups. Group A was considered as non-treated control (NT) (n=8) and fed on standard mice pellet and fresh drinking water. Another group was considered as butter group (n=32), fed on standard mice pellet enriched with 10% butter and after 5 weeks, mice of butter group were subdivided into 4 equal groups (n=8). Group B was considered as butter treated (BT) group fed on standard mice pellet enriched with 10% butter. Group C (C1%), group D (C2%) and group E (C3%) fed on standard mice pellet enriched with 10% butter plus curcumin 1%, 2% and 3% in drinking water respectively. The experiment was carried out for period of another 10 weeks. Body weight gain of all mice was gradually increased and maximum weight gain was recorded in mice of butter fed group. Supplementation of curcumin to butter treated mice (group C, D and E) prevented weight gain. Mice treated with butter fat had significantly (p<0.01) higher hemoglobin (Hb) concentration, total erythrocyte count (TEC) and packed cell volume (PCV). Treatment with curcumin of 1%, 2%, and 3% concentration on butter supplemented mice didn’t alter or rather enhanced the hematological values. In case of lipid profile, supplementation of butter fat in feed significantly increased the total cholesterol, triglycerides and LDL cholesterol. However, addition of curcumin extracts of 1%, 2% and 3% concentration to the butter fed group mice dramatically reduced the total cholesterol and LDL-cholesterol values and more prominent result was observed in 2 % curcumin treated mice. Histo-pathological studies of liver and aorta revealed that addition of 10% butter to feed induced a few fatty changes along with pyknotic nuceli in the hepatocytes, thickened wall of aorta with disorganized lining cells. Again upon curcumin treatment, no such changes were detected in the liver and aortic tissues of group C, group D and group E. Our study revealed that the butter fats have harmful effects on weight gain, on lipid profile and on organ structures without deteriorating normal hematological values. However, these harmful effects could be mitigated by addition of curcumin extracts. J. Bangladesh Agril. Univ. 17(2): 220–225, June 2019